2003
DOI: 10.1128/mcb.23.6.1994-2008.2003
|View full text |Cite
|
Sign up to set email alerts
|

Two Domains of the Progesterone Receptor Interact with the Estrogen Receptor and Are Required for Progesterone Activation of the c-Src/Erk Pathway in Mammalian Cells

Abstract: Steroid hormones influence a plethora of cellular functions, depending on the nature of the target cell and the constellation of signals impinging on the cell at a given time. To achieve the necessary coordination with other signaling pathways in the complex intracellular space, steroid hormones likely use a variety of mechanisms. Until very recently, attention has mainly been focused on the transcriptional effects of steroid hormones. These responses are mediated by the intracellular hormone receptors, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
178
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(183 citation statements)
references
References 43 publications
4
178
1
Order By: Relevance
“…The requirement of Src activity for caveolin-1 activation has already been acknowledged (Li et al, 1996;Lee et al, 2000;Volonte et al, 2001). In addition, accumulating data (Migliaccio et al, 1998;Castoria et al, 1999;Boonyaratanakornkit et al, 2001;Ballare et al, 2003), including our own findings (Proietti et al, 2005), have evidenced progestins ability to induce c-Src phosphorylation by a nongenomic mechanism in mammary tumor cells. Thus, we have recently shown that MPA treatment of C4HD cells for 2-5 min induced strong c-Src tyrosine phosphorylation, which was significantly inhibited by the selective Src kinase family inhibitor PP2 (Proietti et al, 2005).…”
Section: Resultsmentioning
confidence: 60%
“…The requirement of Src activity for caveolin-1 activation has already been acknowledged (Li et al, 1996;Lee et al, 2000;Volonte et al, 2001). In addition, accumulating data (Migliaccio et al, 1998;Castoria et al, 1999;Boonyaratanakornkit et al, 2001;Ballare et al, 2003), including our own findings (Proietti et al, 2005), have evidenced progestins ability to induce c-Src phosphorylation by a nongenomic mechanism in mammary tumor cells. Thus, we have recently shown that MPA treatment of C4HD cells for 2-5 min induced strong c-Src tyrosine phosphorylation, which was significantly inhibited by the selective Src kinase family inhibitor PP2 (Proietti et al, 2005).…”
Section: Resultsmentioning
confidence: 60%
“…In their model, activation of cSrc and the MAPK pathway by progestins depends upon the presence of unliganded ERα, which interacts constitutively with PR-B via two domains that flank the proline-rich sequence of PR. Deletion of either of these two ER-interacting domains in PR-B blocked c-Src/MAPK activation by progestins in the presence of ERα [61]. Mutation of PR-B's PXXP domain had no effect.…”
Section: Extranuclear Actions Of Prmentioning
confidence: 94%
“…Ballare et al [61] reported that MAPK activation by progestins is blocked by antiprogestins and antiestrogens in COS-7 cells transfected with both PR and ERα. They propose that c-Src/ MAPK activation by PR is mediated indirectly by the interaction of the Src-homology two (SH2) domain of c-Src with phosphotyrosine 537 of ERα [61].…”
Section: Extranuclear Actions Of Prmentioning
confidence: 99%
See 2 more Smart Citations